Molecular dynamics investigation on enhancement of heat transfer between electrified solid surface and liquid water. (October 2018) - Wang, Bing-Bing; Xu, Zhi-Ming; Wang, Xiao-Dong; Yan, Wei-Mon
Highlights: Charges are applied to Cu surfaces to enhance heat transfer on Cu-water interface. Molecular dynamics simulations are employed to reveal the enhancement mechanism. Surface charges increase the attraction interaction between Cu and water. Surface charges improve the mismatch of vibrational properties between Cu and water. Abstract: Interfacial nanolayer acting as a bridge linking a bulk solid phase and a bulk liquid phase has a crucial impact on the heat transfer from the solid to the liquid. In this work, we proposed a promising method to enhance the heat transfer between a Cu surface and liquid water by applying surface charges to the surface, which was expected to change the structure of the interfacial nanolayer. We employed molecular dynamics simulations to verify the effectiveness of the method. Our simulations showed that applying surface charges led to an orientational alignment of water molecules, reducing the spacing between the solid surface and the interfacial nanolayer and increasing the number of water molecules located at the interface nanolayer. Meanwhile, the presence of surface charges also improves the mismatch of vibrational density of states between solid atoms and water molecules. As a results, the heat transfer was enhanced as compared with that without surface charges and the enhancement becomes more remarkeble when applying more surface charges to the Cu surface.